Paradigm shifts in disability models and human rights (2012)
Disability law is a recent entrant in the field of legal research and teaching at many universities internationally- The subject has also not been widely acknowledged in many countries around the world prior to the 1990s This article examines disability from its different developmental phases classified as models of disability, namely the charity model, the medical model, the social model and the human rights model of disability. It evaluates the different models in terms of their historical significance, strengths and defects within the context of human rights theory and practice under International Law as it relates to the rights of persons with disabilities (PWDs). The article considers the human rights model as the outcome of the defects that existed in earlier models and argues that it is a contradiction whenever any entitlements considered as a human right are made contingent upon having a disability or the lack of it. of an individual. It examines the rights of persons with disabilities to human dignity under the United Nations (UN) Convention on the Rights of Persons with Disabilities and its Optional Protocol. It concludes that there is inequality and discrimination where characteristic qualities of disability which are not attributable to a person's action or inaction, or their merits or demerits are applied for the purpose of determining the rights of such a person.